Teaching and Learning Materials - Schneider, Jennifer (Fostering Digitisation and Industry 4.0: Education – Vocation - Industry – Future. New Opportunities and Challenges for European VET. Insights in the DigI-VET Project)

Corona Tracing Apps – Eine Analyse und Strukturierung des europäischen Marktes - Brendel, A.B.; Greve, M.; Masuch, K.; Trang, S. (HMD Praxis der Wirtschaftsinformatik)

Examining the role of stress and information security policy design in information security compliance behaviour: An experimental study of in-task behaviour - Trang, S.; Nastjuk, I. (Computers & Security)

The perils of gamification: Does engaging with gamified services increase users’ willingness to disclose personal information? - Trang, S.; Weiger, W. (Computers in Human Behavior)

Explanation as a Social Practice: Toward a Conceptual Framework for the Social Design of AI Systems - Rohlfing, Katharina J.; Cimiano, Philipp; Scharlau, Ingrid; Matzner, Tobias; Buhl, Heike M.; Buschmeier, Hendrik; Esposito, Elena; Grimminger, Angela; Hammer, Barbara; Haeb-Umbach, Reinhold; Horwath, Ilona; Hüllermeier, Eyke; et al. (IEEE Transactions on Cognitive and Developmental Systems)
One objective of current research in explainable intelligent systems is to implement social aspects in order to increase the relevance of explanations. In this paper, we argue that a novel conceptual framework is needed to overcome shortcomings of existing AI systems with little attention to processes of interaction and learning. Drawing from research in interaction and development, we first outline the novel conceptual framework that pushes the design of AI systems toward true interactivity with an emphasis on the role of the partner and social relevance. We propose that AI systems will be able to provide a meaningful and relevant explanation only if the process of explaining is extended to active contribution of both partners that brings about dynamics that is modulated by different levels of analysis. Accordingly, our conceptual framework comprises monitoring and scaffolding as key concepts and claims that the process of explaining is not only modulated by the interaction between explainee and explainer but is embedded into a larger social context in which conventionalized and routinized behaviors are established. We discuss our conceptual framework in relation to the established objectives of transparency and autonomy that are raised for the design of explainable AI systems currently.
Keywords: Explainability; process ofexplaining andunderstanding; explainable artificial systems

Tax Evasion Penalties and Aggressive Tax Avoidance - Giese, Henning

Towards a Differentiation Perspective on Social Media Platforms’ Affordances and Use Cultures – An organizing Literature Review - Arslan, Kader; Trier, Matthias (Proceedings of the 32nd Australasian Conference on Information Systems (ACIS 2021))
Keywords: Social media platform affordances; Use culture; Facebook; Instagram; Twitter

A Review on Social Media Channel Choice Determinants in Organizations - Arslan, Kader (Proceedings of the 29th European Conference on Information Systems (ECIS 2021))
Keywords: Social media management; Social media; Literature review; Affordances; User behavior; Use culture

Man sieht nur mit dem Herzen gut. Beziehungsgestaltung in der virtuellen Lehre - Daniel-Söltenfuß, Desiree; Fuge, Juliane (Die große Lehre im virtuellen Raum: The Empty Space)

Editorial - Daniel-Söltenfuß, Desiree; Emmler, Tina; Fuge, Juliane (Die große Lehre im virtuellen Raum: The Empty Space)

Should I Follow this Model? The Effect of Uncertainty Visualization on the Acceptance of Time Series Forecasts - Leffrang, Dirk; Müller, Oliver (IEEE Workshop on TRust and EXpertise in Visual Analytics)

Customer Inertia Marketing - Henderson, C. M.; Steinhoff, Lena; Harmeling, C. M.; Palmatier, R. W. (Journal of the Academy of Marketing Science)

An Emerging Theory of Loyalty Program Dynamics - Kim, J. J.; Steinhoff, Lena; Palmatier, R. W. (Journal of the Academy of Marketing Science)

Commentary: Opportunities and Challenges of Technology in Relationship Marketing - Steinhoff, Lena; Palmatier, R. W. (Australasian Marketing Journal)

Loyalty Programs as Travel Companions: Complementary Service Features across Customer Journey Stages - Steinhoff, Lena; Zondag, M. M. (Journal of Business Research)

Consumer Solidarity: A Social-System Perspective on the Glue that Holds Society Together - Alberternst, B.; Steinhoff, Lena; Eggert, A.; Giesler, M. (2021 AMA Winter Marketing Educators’ Conference Proceedings, St. Petersburg)

Understanding and Measuring Consumer Solidarity as a Collective Bond - Alberternst, B.; Eggert, A.; Steinhoff, Lena; Giesler, M. (Proceedings of the 50th European Marketing Academy (EMAC) Conference, Madrid)

Projekt Art-D Grids: Nachhaltige und stabile Microgrids in Afrika - eine Plattform für Forschung und Lehre für die Entwicklung - Krauter, Stefan; Böcker, Joachim; Freitag, Christine; Hehenkamp, Burkhard; Hilleringmann, Ulrich; Temmen, Katrin; Klaus, Tobias; Rohrer, Nicolaus; Lehmann, Sven (Tagungsband des 36. PV-Symposiums, 18.-26 Mai 2021)
Keywords: Art-D; Afrika; Resilienz; Resilience; Grid stability; robustness; microgrids

Stellen und Ausbildung der betrieblichen Ausbilder:innen. Grundannahmen, Transformationsprozesse, Reformdiskurse - Kiepe, Karina

Verstetigung eines Fortbildungsansatzes zu nachhaltigem Wirtschaften und Ausbilden - Kiepe, Karina; Gallas, Ricarda; Rüdebusch, Gerrit (Berufsbildung in Wissenschaft und Praxis)

Überwälzung von Digitalsteuern - Graßl, Benjamin; Giese, Henning (beck.digitax)

Georg Giersberg: die Stimme für die BWL - Asenkerschbaumer, Stefan; Buhl, Hans-Ulrich; Sureth-Sloane, Caren; Weißenberger, Barbara E. (Frankfurter Allgemeine Zeitung)

Umfrage: Steuerliche Belastung deutscher Unternehmen – Steuerlast und Verwaltungskosten - Fochmann, Martin; Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren

Digitalisation in the Classroom – Learning Tools - Schneider, Jennifer Nicole (Fostering Digitisation and Industry 4.0: Education – Vocation - Industry – Future. New Opportunities and Challenges for European VET. Insights in the DigI-VET Project)

Fostering Digitisation and Industry 4.0: Education – Vocation – Industry – Future. New Opportunities and Challenges for European VET. Insight in the DigI-VET Project

Förderung von Digitalisierung und Industrie 4.0: Bildung – Beruf – Industrie – Zukunft. Neue Möglichkeiten und Herausforderungen für die europäische Berufsbildung. Einblick in das Projekt DigI-VET - Beutner, Marc; Schneider, Jennifer Nicole (Industrie 4.0- Eine Einführung in die Ideen und neuen Möglichkeiten)

Digitale Prozessintegration in berufs- und wirtschaftspädagogischen Studiengängen – Überlegungen zur Professionalität und professionellen Entwicklung - Jenert, Tobias; Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik – online)

Anderssein als Ressource: Habitus und Habitusreflexion in der Lehrer*innenbildung - Jenert, Tobias (PraxisForschungLehrer*innenbildung)
Lehrer*innen können dazu beitragen, dass bestehende soziale Ungleichheiten verstärkt oder auch abgebaut werden. Eine wichtige Rolle spielen dabei der sogenannte Habitus der Lehrer*innen und dessen (Nicht-)Passung zur sozialen Herkunft der Schüler*innen. In diesem Text stelle ich die Frage, wie angehende Lehrer*innen im Studium unterstützt werden können, die Bedeutung eigener habitueller Prägungen für das professionelle Handeln als Lehrperson zu reflektieren. Ganz besonders befasse ich mich mit der Rolle der Lehrer*innenbildner*innen bei der Förderung von solchen habitusreflexiven Kompetenzen. Hier spielen das Selbst der Hochschullehrenden und die bildungsbiographischen Erfahrungen, die auf dem Weg in die Hochschule gemacht wurden, eine wichtige Rolle.

Digitale Prozessintegration in der beruflichen Lehrer*innenbildung – Praxisnahe Einblicke in die Entwicklung des wirtschaftspädagogischen Studienangebots an der Universität Paderborn - Sänger, Niklas

Einblicke in die curriculare Entwicklung des wirtschaftspädagogischen Studienangebots mit Hilfe der Fallstudiendidaktik - Sänger, Niklas

Soziale Netzwerke als Treiber und Qualitätsmerkmal einer lehrbezogenen Hochschulentwicklung - Sänger, Niklas; Jenert, Tobias

Bausteine der didaktischen Fallstudienentwicklung für die beruflichen Lehrer*innenbildung im Projekt DiPoLe - Sänger, Niklas

Lehrentwicklungs-Netzwerke und institutionelle Ideen der Hochschullehre - Sänger, Niklas; Jenert, Tobias

Lehrentwicklung an Hochschulen als transferorientierte Netzwerkarbeit: Das Bündnis für Hochschullehre Lehren - Jenert, Tobias; Bosse, Elke (Transfer von Innovation und Wissen)

From entrepreneurial experience to expertise: A self-regulated learning perspective - Winkler, Christoph; Fust, Alexander; Jenert, Tobias (Journal of Small Business Management)
Keywords: Management of Technology and Innovation; Strategy and Management; General Business; Management and Accounting

Gestaltung von Studienangeboten. Konzepte, Modelle, Perspektiven - Jenert, Tobias (Handbuch Hochschuldidaktik)

The interplay of personal and contextual diversity during the first year at Higher Education: Combining a quantitative and a qualitative approach - Jenert, Tobias; Brahm, Taiga (Frontline Learning Research)
Research on student transition into Higher Education (HE) has taken different theoretical perspectives. First, studies investigated personal variables such as students´ self-efficacy, emotions and motivation regarding the transition from school to HE. A second strand of research focused on contextual variables, for instance college effectiveness research. With this paper, we combine both the personal and the contextual approach. We aim to investigate the interaction between personal and contextual diversity during the transition into HE, taking into account students’ diversity in particular with regard to gender and individual characteristics, such as self-efficacy. We explored the heterogeneity in students’ personal characteristics by conducting a latent profile analysis (LPA) based on students’ intrinsic motivation, self-efficacy and anxiety before entering Higher Education. LPA resulted in three distinct profiles, with significant differences in how students perceived the first year. This finding suggests that students’ personal characteristics when entering Higher Education influence how they experience the study environment. To investigate the interplay between individual and contextual differences in more detail, we conducted a qualitative longitudinal study with 14 first-year students in parallel with the panel survey. We found that individual students react very differently to specific characteristics and events of the first-year environment. Our study adds to the growing body of research that aims to grasp the complexity of interactions between individual and contextual differences. Specifically, we illustrate how combining quantitative and qualitative methods can provide new insights into person-context interactions.
Keywords: Education

Curriculumforschung - Jenert, Tobias (Handbuch TransdisziplinÃ¤re Didaktik)

Is Consistency the Panacea? Inconsistent or Consistent Tax Transfer Prices with Strategic Taxpayer and Tax Authority Behavior - Diller, Markus; Lorenz, Johannes; Schneider, Georg; Sureth-Sloane, Caren

The Tax Complexity Index – A Survey-Based Country Measure of Tax Code and Framework Complexity - Hoppe, Thomas; Schanz, Debora; Sturm, Susann; Sureth-Sloane, Caren
This paper introduces an index that captures the complexity of countries’ corporate income tax systems faced by multinational corporations. It is based on surveys of highly experienced tax consultants of the largest international tax services networks. The index, called the Tax Complexity Index (TCI), is composed of a tax code subindex covering tax regulations and a tax framework subindex covering tax processes and features. For a sample of 100 countries for the year 2016, we find that the level of tax complexity varies considerably across countries, while tax code and framework complexity also vary within countries. From a global perspective, tax complexity is strongly driven by the complexity of both transfer pricing regulations in the tax code and tax audits in the tax framework. When analyzing the associations with other country characteristics, we identify different correlation patterns. For example, tax framework complexity is negatively associated with countries’ governance, suggesting that strongly governed countries tend to have less complex tax frameworks, while tax code complexity is positively associated with the statutory tax rate, indicating that high-tax countries tend to have more complex tax codes. However, none of the observed associa-tions are very strong. We conclude that tax complexity represents a distinct country charac-teristic and propose the use of our TCI and its subindices in future research.

Share Price Reactions to Tariﬀ Imposition Announcements in the Trump Era – an Event Study of the Trade Conﬂict - Wengerek, Sascha Tobias; Uhde, André
Employing a unique sample of 2,849 tariﬀ imposition announcements by and against the United States (U.S.) over the period from 2018 to 2019, this study analyzes the impact of recent tariﬀ announcements on share prices from 859 U.S. companies. We provide evidence for negative (cumulative) average abnormal stock returns due to tariﬀ announcements during a symmetric three-day event window. We suggest that stock market investors expect adverse impacts of tariﬀ impositions, e.g. a decrease in the companies’ future cash ﬂows and a threat of retaliation. The negative wealth eﬀects are observed irrespective of whether the Trump administration announces safeguard tariﬀs to protect domestic ﬁrms or a retaliation is declared by foreign countries. Moreover, building several subsamples, we ﬁnd that the adverse impact is mostly driven by announcements involving China and is associated with a variety of sector, tariﬀ, trade and ﬁrm characteristics.
Keywords: event study; international relations; protectionism; strategic trade policy; tariﬀs; trade conﬂict

CDS investors’ risk perceptions of M&A announcements - Hippert, Benjamin; Uhde, André
We merge a sample of 492 merger and acquisition (M&A) announcements from 284 acquiring firms across North America and Europe with data from 5-year single-name credit default swaps (CDSs) that are written on stock-listed acquiring firms between 2005 and 2018. Subsequently, we empirically analyze the CDS investors’ risk perception of M&A announcements using event study methodologies. As a baseline finding, we provide evidence for significantly positive cumulative average abnormal CDS spread changes suggesting that CDS investors perceive an increase in the acquiring firms’ credit risk exposures due to M&A announcements. Our baseline finding holds under several robustness checks, especially when controlling for the robustness of the empirical design as well as regional and sectoral differences. Moreover, results from a large variety of sensitivity analyses including deal and firm characteristics provide a deeper insight into the driving factors of CDS investors’ risk perceptions of M&A announcements.

Risk allocation through securitization - Evidence from non-performing loans - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias
Employing a unique and hand-collected dataset of securitization transactions by European banks, this paper analyzes the relationship between true sale loan securitization and the issuing banks’ non-performing loans to total assets ratios (NPLRs). We provide evidence for an NPLR-reducing effect during the boom phase of securitizations suggesting that banks (partly) securitized NPLs as the most risky junior tranche. In contrast, we find the reverse effect during the crises period indicating that issuing banks demonstrated `skin in the game'. A variety of sensitivity analyses provides further important implications for the vital debate on reducing NPL exposures and regulating securitization markets.
Keywords: European Banking; Non-performing Loans; Risk Allocation; Securitization

Transforming into a Platform Provider: Strategic Options for Industrial Smart Service Providers - Beverungen, Daniel; Kundisch, Dennis; Wünderlich, Nancy (Journal of Service Management)
Purpose The purpose of this paper is to identify strategic options and challenges that arise when an industrial firm moves from providing smart service toward providing a platform. Design/methodology/approach This conceptual study takes on a multidisciplinary research perspective that integrates concepts, theories and insights from service management and marketing, information systems and platform economics. Findings The paper outlines three platform types – smart data platform, smart product platform and matching platform – as strategic options for firms that wish to evolve from smart service providers to platform providers. Research limitations/implications Investigating smart service platforms calls for launching interdisciplinary research initiatives. Promising research avenues are outlined to span boundaries that separate different research disciplines today. Practical implications Managing a successful transition from providing smart service toward providing a platform requires making significant investments in IT, platform-related capabilities and skills, as well as implement new approaches toward relationship management and brand-building. Originality/value The findings described in this paper are valuable to researchers in multiple disciplines seeking to develop and to justify theory related to platforms in industrial scenarios.
Keywords: Smart service; Platform; Interdisciplinary research; Manufacturing company; Smart service provider; Platform economics; Information systems; Multi-sided markets; Business-to-business (B2B) markets

Tax Burden on German Companies – Income Tax Burden and Administrative Costs - Fochmann, Martin; Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren

A fuzzy weighted influence non-linear gauge system with application to advanced technology assessment at NASA - Tavana, Madjid; Mousavi, Hossein; Khalili Nasr, Arash; Mina, Hassan (Expert Systems with Applications)

An integrated data envelopment analysis and life cycle assessment method for performance measurement in green construction management - Tavana, Madjid; Izadikhah, Mohammad; Farzipoor Saen, Reza; Zare, Ramin (Environmental Science and Pollution Research)

An integrated fuzzy sustainable supplier evaluation and selection framework for green supply chains in reverse logistics - Tavana, Madjid; Shaabani, Akram; Santos-Arteaga, Francisco J.; Valaei, Naser (Environmental Science and Pollution Research)

An integrated fuzzy AHP- fuzzy MULTIMOORA model for supply chain risk-benefit assessment and supplier selection - Tavana, Madjid; Shaabani, Akram; Mansouri Mohammadabadi, Soleyman; Varzgani, Nilofar (International Journal of Systems Science: Operations & Logistics)

An epsilon-based data envelopment analysis approach for solving performance measurement problems with interval and ordinal dual-role factors - Ebrahimi, Bohlool; Tavana, Madjid; Kleine, Andreas; Dellnitz, Andreas (OR Spectrum)